Pengaruh PMO (pornografi, masturbasi, dan orgasme) terhadap kesehatan mental dan kepribadian pemuda - Maulana, Muhammad Dimas (Maliki Interdisciplinary Journal, 2024)
Pornography, Masturbation, and Orgasm (PMO) have become a complex phenomenon that significantly affects the mental health and personality development of youth in the digital era. This research examines the multidimensional impact of PMO on the psychological, neurological and social structure of the younger generation. Through a comprehensive approach based on a literature review and psychological analysis, this research reveals that repeated exposure to pornography and PMO behavior can result in structural changes in the brain, disrupting the reward system, including impulse control abilities. The results showed a strong correlation between chronic PMO and an increased risk of mental health disorders, including depression, social anxiety, and emotional dysfunction. In terms of personality, individuals who are intensively exposed to PMO tend to experience decreased self-esteem, difficulty building interpersonal relationships, and distortion of self-concept. Factors such as genetics, social environment, and age developmental stage play a significant role in determining the intensity of the impact. This research emphasizes the importance of a holistic approach through comprehensive education, psychological intervention, and empowering the positive potential of youth. The main recommendations include the development of family and educational institution-based prevention strategies, the provision of counseling services, and the creation of an environment that supports optimal mental health and personality development. This study contributes to an in-depth understanding of the psychosocial challenges facing young people in the contemporary digital context.